#TITLE_ALTERNATIVE# - WICAKSONO (NIM 19005058), BAGUS
Based on the fact in Indonesia, there is a growth of mobile phone and PDA user. It has a tendency that mobile phone and PDA have become a necessary need for Indonesian people. Also, since mobile phone and PDA tend to be fashion products, it has a tendency that these products will be popular if it is become preference in one community. There are people who adopt and actually purchase the products at the very first time after the products release. The people are called the innovators. Based on the research that has been conducted by several experts, these people are also might be opinion leaders. These people will offer advices or information to the people surrounding them about new products, services or technologies. In foreign countries, innovators are an early customer of a product or technology. The companies try to involve these people as a part of their marketing strategy. The companies support these people with information or even assistance of their new products. As a result, the companies will get early revenue and if the product is successfully adopted by these people, it might also be adopted by the people surrounding them by word of mouth communication. Here in Indonesia, the companies does not involve the innovators as a part of their marketing strategy. They tend to use above the line marketing strategy which is costly. The problem of the research is that there is lack of companies' understanding related to their customers and the incapability of companies in recognizing correlation between consumer innovators and opinion leaders. Those problems imply the companies believe that consumer innovators in Indonesia are not opinion leaders in their community. Therefore, the researcher conducted a research which the objective is to figure out whether there is a correlation between consumer innovativeness (development concept of innovativeness) and opinion leadership (word of mouth communications). To complete this research, researcher has conducted research by spreading 97 questionnaires in mobile phone and PDA community which exist in several forums in internet. Based on the finding of this research, there is strong and positive correlation between consumer innovators and opinion leaders. However, the number of respondents who are consumer innovators and also opinion leaders is less than the number of respondents who are not consumer innovators but have a role as opinion leaders. Therefore, the policy that has been set up by most of mobile phone and PDA companies which is not supported consumer innovators is right. The recommendation for mobile phone and PDA companies in Indonesia is the companies should focus on non consumer innovators who also have a role as opinion leaders. Since the result showed that the number of respondents who are categorized as non consumer innovators and have a role as opinion leaders is quite high, compared to consumer innovators and who are also opinion leaders, the companies have to deliver their products' advertising as easy as possible to be accepted by these people. They also have to be informed and they have to be assisted in using companies' newest products. So, they would be more knowledgeable and may become consumer innovators in the future.